Lessons from media darlings: gender, context and celebrity culture - Suparsad, Viraj (My University, 2015)
In examining select media coverage of media darlings Khanyi Mbau and Deepika Padukone this study explores the manner in which South African and Indian media shape public understandings of gender. Theoretically centred within the realms of celebrity culture and postfeminism this study explores the role the media plays in the process of teaching the audience about gender, which is notably a learned experience. Furthermore, the study examines the ideals of gender that are disseminated through the content about the media darlings in question.